Women and Men in Rural Microfinance: The Case of Jordan - Hans Dieter Seibel; Gloria Almeyda; Annina Lubbock; Henri Dommel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2002)
Rajwa is a 50 years old widow in the area of Karak, with five children. Her husband died 10 years ago. In January 2000, she received a collateral-free loan of JD 2,100 (US 3,000) from the ACC/IFAD Income Diversification Project, repayable over 8 years. She bought 20 sheep, which have increased to 24, and went into dairy production. By September 2001, she had sold only 2 kg of goat butter and 6 kg of jameed. Everybody produces jameed and butter, there is no market, she says. She has made two payments of JD 30 each, which covers less than the interest due. ACC keeps writing letters and visiting her, but to no avail. With a loan of JD 200 for 8 months, less than one-tenth of the actual loan amount and period, Rajwa could have purchased the equipment and bought milk for dairy production instead of raising sheep. This would have given her the opportunity of testing the market and her entrepreneurial skills at a manageable risk. Now she is stuck with a bad loan and ineligible for another to go into a more profitable line of business. It was the loan terms imposed on her that made her start big - and fail big. She would like to apply for a loan to buy a sewing machine at a cost JD 120; but she is a defaulter, and the amount is too small to be financed from an ACC loan.
Keywords: 330; Mikrofinanzierung; Ländlicher Finanzmarkt; Agrarkredit; Geschlecht; Frauenpolitik; Jordanien